Sharpening the tip of the spear: Tailoring performance psychology for Special Operation Forces - Ytterbøl, Christian; Collins, Dave; MacPherson, Alan (Frontiers in Psychology, 2022)
As performance psychology expands to address different environments, military settings are viewed as a natural extension. In certain cases, however, we suggest that a sub-optimal approach has been employed, due to a lack of specific knowledge of military culture and context, coupled with a diminished emphasis on conducting psychological research targeted directly on military performance. In this paper we explore the specific and importantly unique challenges encountered when researching and consulting with Special Operation Forces (SOF) within the North Atlantic Treaty Organization (NATO) alliance. To support both researchers and practitioners, we offer an overview of the current state of knowledge in this specific domain. We highlight key differences between SOF and conventional forces, then look at the specific requirements for developing performance psychology in the SOF context. Finally, we offer some perspectives on where opportunities might have been missed and offer some suggestions for more impactful (and accurate) research and practice.